PENGARUH PENGUMUMAN SAHAM BONUS TERHADAP VOLUME PERDAGANGAN SAHAM - Ardiansyah R. (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2002)
The aim of this research is to test the information content from the announcement of share bonus. For that research is rarely to be observed. However, that research can use the near theory, like stock split and stock dividend. That announcement can be the one classified, it can be said the other term is stock distribution.This research is to use the secondary data and the measurement is called the trading volume actilAty. The reason of using of that measurement, because it is the important thing, beside the stock price. By observing the trading volume activity it can be seen the fluctuation of the meeting from the demand and supply side. For knowing the significant of changing in the trading volume activity can be measured by approaching the compare mean, that approaching is to compare between before and after share announcement. That event could be a signal for the stock market and it is having the information contentFor this research, it also use the earning growth, that earning is usually as a indicator of good or bad performance from the company condition. This can describe what the companies look. And also this can add the research analysis, then more supported. And that research can be the combination of analysis method between the fundamental and technical analysis.The result of this research indicates, the event can affect the trading volume for all companies and for companies in non-manufacturing and also for in the crisis period. But the market reaction tend to the negative reaction by assuming that there is no spread information before that event.Keywords: Sham bonus, trading volume activity and earning growth.